Are the Loan Loss and Fair Value Components of Bank Income Rationally Priced? - LIM, Chu Yeong (Institutional Knowledge at Singapore Management University, 2013)
This paper examines if the market rationally prices the loan loss provisions, and the fair value gains and losses of US banks. We also model the discretionary components of loan loss provisions and fair value gains and losses, and test if the discretionary components are priced differently from their non-discretionary counterparts. We find little evidence that the market misprices operating cash flows, non-discretionary loan loss provisions, or fair value gains and losses (discretionary or otherwise). However we do find evidence of significant mispricing of discretionary loan loss provisions. This evidence remains significant even after controlling for the fact that loan loss provisions are correlated with bank risk.